Localized Video Clip Presentation in Improving The Level of Performance in Science of Grade-IV Learners in The Remote Area Schools at San Marcelino District - Tiburcio, Cesar A. (Future Science / FSH-PH Publications, 2024)
The study determined the effects of localized video presentation Science grade four learners at Sa Marcelino District. In this study, the quasi-experimental design is used in the study, Pre-test and post was administered in the study to determine the effects of the localized video presentation. The result indicates that localized video presentation has a significant difference in improving the performance of the grade four learners in Science. Moreover, the level of performance of the learners have a positive correlation on the use of intervention. Thus, the researcher recommends to develop and conduct another study in using localized video presentation to improve the performance of their study.